2016
DOI: 10.1111/ens.12206
|View full text |Cite
|
Sign up to set email alerts
|

Flower visitation patterns of the coexisting honey bees Apis cerana japonica and Apis mellifera (Hymenoptera: Apidae)

Abstract: We compared flower visitation patterns of two coexisting honey bees, Apis mellifera Linnaeus and Apis cerana japonica Radoszkowski, on 20 plant species, including three exotics, under natural conditions in Nara, Japan, from April to August 2012. We also measured flower color based on bee color vision (15 flower species), nectar volume (nine species) and nectar concentration (eight species). Flowers colored white, pink, red, purple and cream were classified as bee‐blue‐green, and yellow was classified as bee‐gr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
14
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(15 citation statements)
references
References 57 publications
1
14
0
Order By: Relevance
“…Indeed, diet has been shown to have an impact on diversity in the gut microbiota in multiple studies, with, for example, a reduction of diversity reported for the human gut microbiota as a consequence of westernized diet [ 57 , 58 ]. As of yet, large-scale systematic studies on the foraging preferences of A. cerana and A. mellifera have not been conducted, but they appear to have largely overlapping foraging ranges in Asia [ 59 , 60 ]. Further studies are therefore needed to determine whether differences in strain-level diversity are related to dietary differences.…”
Section: Discussionmentioning
confidence: 99%
“…Indeed, diet has been shown to have an impact on diversity in the gut microbiota in multiple studies, with, for example, a reduction of diversity reported for the human gut microbiota as a consequence of westernized diet [ 57 , 58 ]. As of yet, large-scale systematic studies on the foraging preferences of A. cerana and A. mellifera have not been conducted, but they appear to have largely overlapping foraging ranges in Asia [ 59 , 60 ]. Further studies are therefore needed to determine whether differences in strain-level diversity are related to dietary differences.…”
Section: Discussionmentioning
confidence: 99%
“…, Kim and Smith ), but can make use of a wide range of nectar concentrations (Biesmeijer et al. , Tatsuno and Osawa ). However, Somme et al.…”
Section: Introductionmentioning
confidence: 99%
“…Indeed, diet has been shown to have an impact on diversity in the gut microbiota in multiple studies, with for example a reduction of diversity reported for the human gut microbiota as a consequence of westernized diet [43, 44]. As of yet, large-scale systematic studies on the foraging preferences of A. cerana and A. mellifera have not been conducted, but they appear to have largely overlapping foraging ranges in Asia [45, 46]. Further studies are therefore needed to determine whether differences in strain-level diversity are related to dietary differences.…”
Section: Discussionmentioning
confidence: 99%